Non-destructive insights into photosynthetic and photoprotective mechanisms in Arabidopsis thaliana grown under two light regimes - Vítek, P; Mishra, K B; Mishra, A; Veselá, B; Findurová, H; Svobodová, K; Oravec, M; Sahu, P P; Klem, K (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2022)
Probing insights into understanding photosynthetic processes via non-invasive means has an added advantage when used in phenotyping or precision agriculture. We employed Raman spectroscopy and fluorescence-based methods to investigate both the changes in the photosynthetic processes and the underlying protective mechanisms on Arabidopsis thaliana wild-type (WT), and ros1, which is a mutant of a repressor of transcriptional gene silencing, both grown under low light (LL: 100 μmol m-2s-1) and high light (HL: 400 μmol m-2s-1) regimes. Raman imaging detected a lower carotenoid intensity after two weeks in those plants grown under HL, compared to those grown under the LL regime; we interpret this as the result of oxidative damage of β-carotene molecules. Further, the data revealed a significant depletion in carotenoids with enhanced phenolics around the midrib and tip of the WT leaves, but not in the ros1. On the contrary, small necrotic zones appeared after two weeks of HL in the ros1 mutant, pointing to the starting oxidative damage. The lower maximum quantum yield of the photochemistry (Fv/Fm) in the WT as well as in the ros1 mutant grown in HL (compared to those in the LL two weeks post-exposure), indicates the HL partially inactivated photosystems. Chlorophyll a fluorescence imaging further showed high non-photochemical quenching (NPQ) in the plants grown under the HL regime for both the WT and the ros1 mutant, but the spatial heterogeneity of NPQ images was much higher in the HL-grown ros1 mutant. Fluorescence screening methods revealed significantly high values of chlorophyll proxies in the WT as well as in the ros1 mutant two weeks after in the HL compared to those under LL. The data generally revealed an increased accumulation of phenolics under HL in both the WT and ros1 mutant plants, but the proxies of anthocyanin and flavonols were significantly lower in the ros1 mutant than in the WT. The comparatively low accumulation of anthocyanin in the ros1 mutant compared to the WT supports the Raman data. We conclude that integrated use of these techniques can be efficiently applied for a better understanding of insights into photosynthetic mechanisms.
Keywords: listy rostlin; Light stress; tyrosinkinasy; fotosyntéza; Arabidopsis; fotosystém II (proteinový komplex); chlorofyl a; anthokyaniny; Phenotyping; Photosynthesis; Chlorophyll; Proto-Oncogene Proteins; Raman spectrometry; Bioimaging; Chlorophyll A; Light acclimation; světlo; chlorofyl; Carotenoids; Plant Leaves; Photosystem II Protein Complex; Anthocyanins; Light; Protein-Tyrosine Kinases; protoonkogenní proteiny; Chlorophyll a fluorescence; karotenoidy